2020
DOI: 10.1097/sap.0000000000002199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polycaprolactone/Gelatin/Chitosan Electrospun Membrane for Peritoneal Adhesion Reduction

Abstract: In this study, a novel antiadhesion membrane made of polycaprolactone, gelatin, and chitosan was fabricated using the electrospinning technique. A series of polycaprolactone/gelatin/chitosan (PGC) electrospun membranes with different amounts of chitosan (0%, 0.5%, 1%, and 2% in weight percentage) was synthesized. The physicochemical properties and biocompatibility of the fabricated membranes were examined and compared with the aim to select an effective antiadhesion membrane. Scanning electron microscopy showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Adapted with permission. [218] Copyright 2020, Wolters Kluwer Health, Inc. F) Adhesion areas and scores in different treatment groups. Adapted with permission.…”
Section: Abdominal Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adapted with permission. [218] Copyright 2020, Wolters Kluwer Health, Inc. F) Adhesion areas and scores in different treatment groups. Adapted with permission.…”
Section: Abdominal Adhesionmentioning
confidence: 99%
“…Therefore, PGC electrospun membranes can be used in postoperative anti-adhesion applications. [218] In addition, mechanical injury, infection, and foreign body reaction during abdominal surgery promotes the production of ROS, which promotes vascular permeability. The increase of inflammation aggravates ROS reactions and promotes the formation of coagulation and fibrin.…”
Section: Abdominal Adhesionmentioning
confidence: 99%
“…Surgery, trauma, chronic peritoneal inflammation, peritoneal dialysis, endometriosis, etc., can induce PA formation [ 3 , 4 , 5 , 6 , 7 ]. However, most PAs are caused by surgery [ 8 , 9 , 10 ]. PAs can cause pain, female infertility, intestinal obstruction, and other problems, and bring difficulties to reoperation [ 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCL, as a biocompatible and slow biodegradable polyester, possesses the property of antiadhesiveness, frequently used for this aim. It brings several benefits such as cost-effectiveness, great blend compatibility, food and drug administration (FDA) approval, low protein/cell adhesion tendency in proportion to its wettability, stability in aqueous conditions, availability in mass production, and appropriate mechanical properties. ,, However, it is suggested that PCL should be blended with other polymers with a high biodegradable rate since its brittle properties, long-lasting PCL, and slow degradation are drawbacks to the wound healing process and biocompatibility at the wound site . To deal with this issue, more research has used PCL-blended PEG, chitosan, gelatin, hyaluronic acid, PLGA, and PLA. ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…4 To deal with this issue, more research has used PCL-blended PEG, chitosan, gelatin, hyaluronic acid, PLGA, and PLA. 4,10,26,32,33 The possibility of fibrin bond formation is very high immediately after surgery until the next 3 days. 2,7 It is highly recommended that the presence of a chemical barrier alongside a physical one helps the inflamed surgery site to be manipulated to normal situations.…”
Section: Introductionmentioning
confidence: 99%